Farmers’ Outlook on Agricultural Subsidies in Punjab - Anupam Anand and Manmeet Kaur (Indian Journal of Extension Education, 2018)
Agriculture subsidies are given by centre as well as state governments to the farmers. There are two motivesbehind providing the agricultural subsidies to farmers; firstly to encourage the use of new technology amongthe farmers and secondly to reduce the cost of production. This study was conducted in order to get an insightinto the farmers’ perspective on agricultural subsidies in Punjab. Ninety beneficiary and ninety non-beneficiaryfarmers were selected from the three agro-climatic zones of Punjab. Majority of the farmers agreed thatsubsidies help to increase production but at the same time were making the farmers more dependent on thegovernment. The non-beneficiary farmers perceived that subsidies are biased towards large farmers. Asignificant difference was found in the variables viz. operational land holding, annual income and mass mediaexposure of the beneficiary and non-beneficiary farmers. Tobit regression analysis showed that farmers’operational holding, lack of awareness of time of availability of subsidy, delay in release of subsidies andmisallocation of the subsidies significantly affected the receipt of subsidy by a farmer. The idea of farmsubsidies being counterproductive finds a strong basis in case of Punjab, where these have started posing athreat not only to the exchequer but also to the sustainability of agricultural operations. Thus, a reorientationin the grant of subsidies is clearly the need of the hour, so that its distorting effects are corrected.